Reclamation of Arid Lands - Jafari, Mohammad (Environmental Science,, 2018)
This book provides an overview of arid and semi-arid lands conditions, their general characteristics, methods of management, conservation, exploitation and reclamation. It also focuses on how to utilize the potential of arid lands with the minimum manipulation and alteration. Arid and semi-arid areas represent a major part of natural ecosystems not only in Iran, but around the world, and mismanagement and inappropriate exploitation of these areas may lead to further gradual degradation. As such, an understanding of the characteristics of these areas is vital if they are to be conserved and reclaimed.